Optimal human being : an integrated multi-level perspective - Sheldon, Kennon M. (Kennon Marshall) (Lawrence Erlbaum Associates, 2004)
The phrase "optimal human being" is used to refer to the empirically documented features that tend to characterize high-quality human functioning. "Optimal human being" is a profile that is developed within this book by consulting what contemporary theorizing at different levels of analysis might have to say about what causes a optimal functioning